2018
DOI: 10.1172/jci.insight.98045
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins E and CIII interact to regulate HDL metabolism and coronary heart disease risk

Abstract: This work was supported by NIH grant R01HL095964 to FMS and by a grant to the Harvard Clinical and Translational Science Center (8UL1TR0001750) from the National Center for Advancing Translational Science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 68 publications
6
83
0
2
Order By: Relevance
“…Current evidence suggests that blood lipid particles are highly heterogeneous and comprise a group of lipoproteins and apolipoproteins (such as apoC and apoE) with diverse biological functions [13,[15][16][17]. For instance, studies have shown that LDL that contains apoC-III, but not LDL that lacks apoC-III, was an independent risk factor for cardiovascular risk [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current evidence suggests that blood lipid particles are highly heterogeneous and comprise a group of lipoproteins and apolipoproteins (such as apoC and apoE) with diverse biological functions [13,[15][16][17]. For instance, studies have shown that LDL that contains apoC-III, but not LDL that lacks apoC-III, was an independent risk factor for cardiovascular risk [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Two independent prospective studies showed that HDL cholesterol that contains or lacks apoC-III demonstrated opposite associations with the risk of coronary heart disease (CHD): HDL cholesterol that lacks apoC-III was inversely associated with CHD, whereas HDL cholesterol that contains apoC-III (small subfraction) was associated with a higher risk of CHD [16]. Further, the associations of apoE concentrations in HDL with cardiovascular risk significantly differ in the presence of apoC-III in that HDL with both apoE and apoC-III tended to be associated with a higher cardiometabolic risk [17,33,34]. Therefore, the heterogeneous lipoprotein subspecies deserve to be characterized in order to improve the disease risk prediction rather than relying on total lipid fractions [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La pacienţii HiV pozitiv, homozigozitatea apo ε4 ne arată progresia spre SiDa şi creşterea susceptibilitităţii la infecţii oportuniste. apoe plasmatică apare în principal prin sinteză hepatică; la nivel cerebral, astrocitele produc o cantitate mare de lichid cefalorahidian ce conţine apoe (23,24,25). aSoCIEREa apoE cu unElE afEcţiuni apo ε4 aste asociată cu boala alzheimer familială cu debut tardiv.…”
Section: Caracteristicile Genotipurilor Apoe (Alele ε2 ε3 ε4)unclassified